Developing a Causal Model to Predict the Stability of Marital Relationship in Couples who are Faced with Unfaithfulness - Malihe Shirdel; Simin Hosseinian; Seyed Ali Kimiaei; Mohammadreza Safarian (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Sustainable marriage is one of the broadest concepts for determining the level of happiness and satisfaction with the relationship. The present study aimed to develop a causal model for predicting the sustainability of couples who are faced with unfaithfulness. Materials and Methods: This study was of correlational design. The statistical population consisted of all married women and men facing unfaithfulness who lived in Bojnourd in 2017-2018. The study population included 203 married people who were randomly selected. To collect data, Walker & Thompson's Intimacy Scale, Gottman couples' confidence test, Gottman couples' sexual attractiveness evaluation, and Gottman couples' relationship stability were used. For data analysis, Pearson correlation coefficient and structural equation modeling were used in SPSS-22 and AMOS-22 software. Results: Increased level of couples' trust with mean (SD) 143.8 (16.3), correlated with increased couples' intimacy with mean (SD) 5.8 (1.1) (P<0.01). Increased level of sexual attractiveness with mean (SD) 69.4 (10.9), correlated with increased stability of couples' relationships with mean (SD) 40.7 (6.1) (P<0.01). In addition, increased level the confidence of couples correlated with increased sexual attractiveness (P<0.01) and couples' relationship stability (P<0.05). Sexual attractiveness (P<0.01) and couples' relationship stability (P <0.01) increased with increasing couples' intimacy. The direct effect of couples' trust on their intimacy was 0.38 and their sexual attractiveness 0.27. Moreover, the indirect effect of couples' trust on sexual attractiveness was 0.06 and the stability of the relationship 0.19. The total effect of trust on couples' intimacy were 0.38, sexual attractiveness 0.33, and the stability of couples' relationship 0.19. Couples' trust, explained 17% of the changes in couples' relationships stability after disclosure of unfaithfulness by couples' intimacy and sexual attractiveness (R2= 0.17). Conclusion: The study showed that the intimacy of couples and sexual attraction played a significant intermediate role in the trust of couples and the sustainability of their relationships. DOI: http://doi.org/10.22037/ch.v5i4.22777